2018
DOI: 10.1177/0042098018763319
|View full text |Cite
|
Sign up to set email alerts
|

The hidden side of the entropy-based land-use mix index: Clarifying the relationship between pedestrian volume and land-use mix

Abstract: This study clarifies the previously unknown limitations of the entropy-based land-use mix index and suggests conditions under which the index is valid. The land-use mix index has an n-shaped relationship to dependent variables, which was evidenced by this study, but previous studies have ignored the problem. This study identified a non-linear relationship between the land-use mix index and a common dependent variable of interest, pedestrian volume. Pedestrian volume is a common measure of the vitality of a dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
31
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 30 publications
4
31
0
2
Order By: Relevance
“…3 Korea Transport Surveys and DB Construction Projects (Korea Transport Institute, 2001) show that different pedestrian volumes are generated through various building use categories: residential is 0.11 person/m 2 /day, commercial is 0.85/m 2 /day, office is 0.35/m 2 /day, and other is 0.33/m 2 /day. Applying these values for CLUM2 in residential and non-residential uses, one can draw a straight line, which is similar to the one that can be drawn for estimated pedestrian volume in Figure 1 (Im and Choi, 2019). This straight line serves as a logical image of the pedestrian volume created when mixing residential and nonresidential uses, and it reconfirms a limitation of CLUM.…”
Section: Pedestrian Volume Clum and The Limitation Of The Indexmentioning
confidence: 61%
See 4 more Smart Citations
“…3 Korea Transport Surveys and DB Construction Projects (Korea Transport Institute, 2001) show that different pedestrian volumes are generated through various building use categories: residential is 0.11 person/m 2 /day, commercial is 0.85/m 2 /day, office is 0.35/m 2 /day, and other is 0.33/m 2 /day. Applying these values for CLUM2 in residential and non-residential uses, one can draw a straight line, which is similar to the one that can be drawn for estimated pedestrian volume in Figure 1 (Im and Choi, 2019). This straight line serves as a logical image of the pedestrian volume created when mixing residential and nonresidential uses, and it reconfirms a limitation of CLUM.…”
Section: Pedestrian Volume Clum and The Limitation Of The Indexmentioning
confidence: 61%
“…Some analyses using the index have not presented statistically positive effects of LUM on pedestrian volume and, in certain cases, have even shown a negative relationship. Im and Choi (2019) found that the LUM index had a critical limitation beyond those already discussed by Kockelman (1996), Brown et al (2009), Hess et al (2001), and others. They confirmed that the conventional entropy-based land use mix index (hereafter, CLUM) has an n-shaped relationship with pedestrian volume and that, in the case of the sample from the whole city, the explanatory power of pedestrian volume increased in the empirical model when using both CLUM and CLUM squared rather than only using CLUM.…”
Section: Introductionmentioning
confidence: 73%
See 3 more Smart Citations